Implementing TPR for Young Learners Vocabulary Mastery - Randy Randy; Nabila Nabila; Ashar Ashar; Harmilawati Harmilawati (Universitas Nurul Jadid, 2026)
Vocabulary mastery plays a crucial role in supporting young learners’ overall English proficiency, particularly in elementary-level contexts where learning typically relies on concrete examples and active engagement. However, many students still experience difficulties in retaining and understanding new vocabulary due to teacher-centered instruction and the limited use of interactive learning methods. To address this gap, this research aims to examine the effectiveness of the Total Physical Response (TPR) method in enhancing students’ English vocabulary mastery, specifically on the topics of body parts and action commands. Employing a quantitative one-group pretest–posttest design, the research involved fifth-grade students at SDN 246 Bulu-Bulu, Tonra District, Bone Regency. Data were obtained through a vocabulary worksheet and a comprehension test designed in accordance with TPR principles, and an 80-minute TPR-based learning session served as the intervention. The results show a notable improvement in students’ vocabulary performance, with mean scores increasing from 64.29 on the pretest to 83.10 on the posttest. A paired sample t-test further confirmed a significant effect of the TPR method on vocabulary mastery, indicated by a t-value of 7.26 exceeding the critical value of 2.086. These findings suggest that TPR effectively supports students’ understanding, memory retention, and participation by integrating physical movement with verbal instruction. Therefore, TPR can be considered an engaging and suitable method for teaching vocabulary to elementary school students, particularly in rural learning environments with limited access to instructional media.